A cross-sectional study to document socio-demographic profile and disease profile of dermatosis in pediatric age group - Jadav, Naresh B.; Vaghela, Nital N.; Patel, Komal B.; Patel, Yogesh U.; Parmar, Brijesh V.; Umarigar, Dipak D. (International Journal Of Community Medicine And Public Health, 2023)
Background: Skin diseases are considered a major health problem in the pediatric age group and are sometimes associated with significant morbidity. Among them, dermatosis is one of the most common skin diseases in India, affecting the skin and hair. Early diagnosis and treatment are essential for pediatric patients to prevent long-term persistence or disability caused by the disease. Although some manifestations are physiological and require no treatment, different age groups have different sets of clinical dermatoses, with dermatitis being the most common among all age groups. Studying the proportions of various clinical presentations of different types of dermatosis helps in the proper diagnosis and management of patients. This study was conducted to document the socio-demographic profile and disease profile of various forms of pediatric dermatosis. Methods: A cross-sectional study was conducted from April 2017 to March 2019 among 401 pediatric patients at a tertiary-level hospital. Results: Out of the 401 participants, approximately two-thirds were male, and more than half (53.1%) were 5-11 years old. Among the dermatoses groups, the most common were dermatitis (20.4%), nutritional (15%), pigmentary (13.6%), and others. Conclusions: All forms were predominantly seen among males, except in a few dermatitis types like papulosquamous, hair, pigmentary, bullous, and keratinizing disorders, where females were more prone than males.